THE EFFECT OF LEVERAGE, WORKING CAPITAL EFFICIENCY, AND VALUE RELEVANCE OF ACCOUNTING INFORMATION ON INVESTMENT DECISIONS WITH DIVIDEND POLICY AS AN INTERVENING VARIABLE - Ilham, Dika Fajri; munandar, agus (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
This research examines the influence of leverage, working capital efficiency, and value relevance of accounting information on investment decisions with dividend policy serving as an intervening variable. The research data source utilizes the financial statements of LQ45 companies from 2019 to 2024 and uses secondary data. The sample for this study consists of 19 companies out of 45 companies obtained using purposive sampling method for 6 consecutive years with dividend distribution. The influence test uses multiple linear regression and mediation analysis through path analysis. The outcomes showed that the independent variables simultaneously influenced the dependent variable in both model 1 and model 2. Only the leverage of the partial test is significant on dividend policy and investment decisions, while dividend policy does not mediate independent variables on investment decisions.